ANALYSIS OF CLASSIFICATION OF BUSINESS TYPES AND GOVERNMENT CONTRIBUTION TO THE DEVELOPMENT OF BUSINESSES MANAGED WITH DISABILITY IN GUNUNGKIDUL DISTRICT - Siti Afidatul Khotijah; Agustina Prativi Nugraheni; Endang Kartini Panggiarti (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study aims to analyze groups of types of businesses run by people with disabilities in Gunungkidul Regency and analyze the role of the government in the development of businesses run by people with disabilities. This study uses purposive sampling where the main requirement is individuals with disabilities who have MSME businesses in Gunungkidul Regency. This research is a descriptive qualitative study. The type of data used in this study is primary data derived from interviews and observations of respondents. The results of this study indicate that the types of businesses run by people with disabilities in Gunungkidul Regency are mostly in the form of services (shaving, massage and sewing), handicrafts, printing and culinary services. The type of business carried out is in accordance with the advantages possessed by Gunungkidul Regency, namely the agricultural, industrial and service sectors. In addition, the government, represented by the Gunungkidul Regency MSME Service, has involved disabilities in the expo activities that were held, but people with disabilities expect more roles from the office for business assistance, starting from improving product quality, marketing to capital.